The Role of Electronic Wallets in Strengthening the Economy of Developing Countries: With reference to Egypt. (Entrepreneurship Journal for Finance and Business, 2024)
E-wallets play an important role in enhancing the size of financial technology in the country by providing a smooth and convenient way for individuals to transact online. E-wallets allow users to store their payment information securely and make transactions with ease.This study aims to demonstrate the role and importance of these portfolios in supporting the economy in countries, especially in Egypt, by enhancing the volume of financial technology and increasing financial inclusion, which helps support the formal economy and increase financial culture, which is an important condition for improving the economic conditions in the country considering these rapid technological developments.